Designing Information Technology to Support Distributed Cognition - Boland, Richard J.; Tenkasi, Ramkrishnan V.; Te'eni, Dov (Organization Science, 1994)
Cognition in organizations is a distributed phenomenon, in which individual members of an organization reflect upon their experience, make plans, or take action. Organizational learning or organizational cognition are familiar terms, but it is only the individual persons in an organization who create interpretations and test understandings, as they think and learn in their organizational setting. Coordinated outcomes emerge in organizations when individuals think and act in ways that take others in the organization and their interdependencies into account. We argue that much of the effort to design information technology to support cognition in organizations has not addressed its distributed quality. Such systems have tended to focus either on the individual as an isolated decision maker, or on the group as a producer of a decision or policy statement in common. In distributed cognition, by contrast, the group is a set of autonomous agents who act independently yet recognize that they have interdependencies. To guide the design of information technology, we propose that distributed cognition be viewed as a hermeneutic process of inquiry, emphasizing the importance of individual interpretation and group dialogue. Hermeneutics provides a theory of the interpretive process through which an individual gives meaning to organizational experience. Inquiry systems provide a theory of how a community of inquirers build and test knowledge representations through dialogue. Together, hermeneutics and inquiry systems are used to propose a set of design principles to guide the development of information technology that supports distributed cognition. The design principles we describe in the paper are ownership, easy travel, multiplicity, indeterminacy, emergence and mixed forms. Applications of information technology which embody these design principles would support distributed cognition by assisting individuals in making interpretations of their situation, reflecting on them, and engaging in dialogue about them with others. The objective is to refine their own understanding of the situation and better appreciate the understandings of others, enabling them to better take their interdependencies into account in their individual actions. A project to develop such a system is discussed, along with some implications for research.